Comparison of Gantry Drive and Crankset: A Pilot Study Across a Broad Power Spectrum - BEREŚ, Łukasz; OBSZAŃSKI, Marcin; PYRZANOWSKI, Paweł (Engineering Transactions, 2025)
The gantry drive was originally invented in 1948 in England and was “rediscovered” in Poland in 2019 while working on lightweight, personal, compact vehicles. In this study, the gantry drive is subjected to dynamic tests against the background of the commonly known crankset. The aim of the dynamic tests is to develop power curves and measure efficiency for various human-mechanism systems, i.e., the hand-driven crankset, the leg-driven crankset, and the gantry drive. Pilot dynamic tests have shown many advantages of the gantry over the crankset; in general, test participants were much less tired when using the gantry drive.